2019
DOI: 10.3748/wjg.v25.i32.4598
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis: Current concepts in diagnosis and treatment

Abstract: Eosinophilic esophagitis is an immune-allergic pathology of multifactorial etiology (genetic and environmental) that affects both pediatric and adult patients. Its symptoms, which include heartburn, regurgitation, and esophageal stenosis (with dysphagia being more frequent in eosinophilic esophagitis in young adults and children), are similar to those of gastroesophageal reflux disease, causing delays in diagnosis and treatment. Although endoscopic findings such as furrows, esophageal mucosa trachealization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 124 publications
1
87
0
14
Order By: Relevance
“…Our study showed that most (86.2%) children had been given a pharmaceutical at some stage to treat their EoE. Reflux medications such as proton pump inhibitors are a first-line treatment option for EoE (7) and were the most commonly used pharmaceutical. However, proton pump inhibitors may be associated with adverse side effects when used for a long term (51), and almost one quarter of those respondents who had used # The total number of practitioners is greater than the number of responses as some respondents listed more than one other practitioner.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our study showed that most (86.2%) children had been given a pharmaceutical at some stage to treat their EoE. Reflux medications such as proton pump inhibitors are a first-line treatment option for EoE (7) and were the most commonly used pharmaceutical. However, proton pump inhibitors may be associated with adverse side effects when used for a long term (51), and almost one quarter of those respondents who had used # The total number of practitioners is greater than the number of responses as some respondents listed more than one other practitioner.…”
Section: Discussionmentioning
confidence: 81%
“…EoE incidence is increasing globally, with an estimated prevalence of one in every 2,000 people (2)(3)(4). International clinical guidelines list EoE first-line treatment options as proton-pump inhibitors, swallowed topical steroids, elimination diets, and elemental formula (5)(6)(7)(8). While there are no national guidelines in Australia for the management of EoE, international guidelines are usually applied (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the role that dietary antigens play in the pathogenesis of this disease. Currently, there are two main choices for initial diet therapy for EoE: elementary diets, based on the administration of simple amino acids, and elimination diets [8]. A group of 10 children with EoE were evaluated through an elementary diet [156].…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%
“…These changes include fixed oesophageal rings (trachealisation), transient rings (felinisation), white exudates, longitudinal furrows, oedema, oesophageal narrowing, mucosal fragility, and a tendency for lacerations (crepe paper oesophagus). In addition to EoE patients with these characteristic changes, a macroscopically-normal oesophagus is also seen in up to 30% of paediatric EoE patients [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum threshold for a diagnosis of EoE is 15 eosinophils per high-power field (hpf) in at least one specimen. Other histopathological changes observed in patients with EoE include eosinophilic micro-abscesses, surface layering of eosinophils, extracellular eosinophil granules, basal cell hyperplasia, lamina propria fibrosis and dilated intercellular spaces [10,11].…”
Section: Introductionmentioning
confidence: 99%